Change and continuity in the role of Kenya’s National Assembly in Formulating Kenya’s Foreign policy; 1900 – 1978: The Influence of Kenya's National Assembly in Foreign Policy - WEHLIYE, ADAN (Advances in Social Sciences Research Journal, 2020)
Globally, parliament’s role in influencing policies is immense. In Kenya, the role of the national assembly in determining the direction and results of foreign policies, although, blurred cannot be underestimated. Kenya became a British protectorate in 1895 with a limited representation of Africans in the legislative Council (LegCo). The role of this minority group in influencing foreign policy, though, rarely documented need not be underestimated. The group threw Kenya into the world map and between 1900-1963, major foreign policy debates in the Council revolved around when and how Kenya was to become a self-governing entity. After gaining independence, new members of parliament had a herculean task of dealing with immediate local needs and debating and most importantly influencing important foreign policies including policies on health, education, debt burden, settler issues and representation of minority groups including whites in the House. With a change of guard from a white-dominated to an almost all African-black faces, the national assembly played an important role in ensuring that policies on health, education, security, trade as well as crafting the path on which foreign policy would take. This paper begins by tracing the evolution of parliament in the colonial administration and reviews the role that Kenyan Parliament played in influencing foreign policy from 1900 to 1978. The paper identifies the actors, their roles and the political context within which these actors and structures operated.